2013
DOI: 10.1097/aog.0b013e31827e5c85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Prenatal Aneuploidy Screening Policies in an Integrated Health Care System

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, unlike our study, the Larion study [16 ]did not examine invasive procedures after second-trimester maternal serum analyte screening. Norton et al [18 ]also published similar findings after the introduction of first-trimester screening with NT and maternal analytes. However, this study did not include the effect of NIPT on invasive testing.…”
Section: Discussionsupporting
confidence: 58%
“…However, unlike our study, the Larion study [16 ]did not examine invasive procedures after second-trimester maternal serum analyte screening. Norton et al [18 ]also published similar findings after the introduction of first-trimester screening with NT and maternal analytes. However, this study did not include the effect of NIPT on invasive testing.…”
Section: Discussionsupporting
confidence: 58%
“…In assessing trends in the use of invasive diagnostic testing among women who delivered at an integrated health care system in California, this study found that the number of amniocenteses or chorionic villus sampling procedures performed as a percentage of the number of deliveries in 2006 was 12%. 17 A minimal detectable difference of 6% was selected (half of the rate in the control group), corresponding to an odds ratio (OR) of 0.47 (a small to medium effect size). To achieve 80% power (2-tailed α = .05; 90% retention at follow-up), the required sample size was 396 per group or 792 in total.…”
Section: Discussionmentioning
confidence: 99%
“…In our study of trends in the use of invasive diagnostic testing among women who delivered at an integrated health care system in California, we found that the number of amniocenteses or CVS procedures performed as a percentage of the number of deliveries in 2006 was 12%. 17 We selected a minimal detectable difference of 6%, or half of the rate in the control group, corresponding to an odds ratio of 0.47 (a small to medium effect size). To achieve 80% power, with a twotailed alpha equal to 0.05 and 90% retention at follow-up, the required sample size was 396 per group, or 792 in total.…”
Section: Discussionmentioning
confidence: 99%